Cybersecurity Policy and Its Implementation in Indonesia - Rizal, Muhamad; Yani, Yanyan (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2016)
The purpose of state defense is to protect and to save the integrity of the Unitary State of the Republic of Indonesia, the sovereignty of the state, as well as its security from all kinds of threats, whether they are military or non-military ones. One of the non-military threats that potentially threatens the sovereignty and security of the nation-state is the misuse of technology and information in cyberspace. The threat of irresponsible cyber attacks can be initiated by both state and non-state actors. The actors may be an individual, a group of people, a faction, an organization, or even a country. Therefore, the government needs to anticipate cyber threats by formulating cyber security strategies and determining comprehensive steps to defend against cyber attacks; its types and the scale of counter-measures, as well as devising the rules of law.Â